Values and their role in competitive sport: In-depth interviews with highly accomplished athletes - Szynkarewicz, J.; Poczwardowski, A. (Studies in Sport Humanities, 2015)
This study explores values from the perspective of positive sport [Poczwardowski, Nowak, Parzelski and Kodecka-Rogalska 2012]. Based on a qualitative research design, in-depth interviews [Silverman 2009] were conducted with 6 athletes representing highest sport success (such as Olympic, World Cup, European Cup, and Polish Cup medallists). Extraction of meaning method [Kvale 2004] was used in the data analysis and consisted of condensation, categorization, and the interpretation of meaning. The participants suggested that their values may have an influence on the quality of their development and their sport performance. Athletes found values as an important part of their professional and personal lives. It should be emphasized that these values are both developed through participating in sport and simultaneously enrich the sport experience. Further, values flow from sport lives to non-sport lives and it is the athletes themselves who integrated these values and catalyzed their flow between sport and non-sport realms.